1767 Validation of the Dutch 60 Months Ages and Stages Questionnaire (ASQ). (October 2012) - Hornman, J; Kerstjens, JM; Winter, AF de; Bos, AF; Reijneveld, SA
Abstract : Introduction: The Ages and Stages Questionnaire (ASQ) is currently the most widely used parent-completed developmental screener. Psychometric properties of the Dutch ASQ 60-months version (Dutch_ASQ-60) have not yet been assessed. Aim: To assess the psychometric properties of the Dutch_ASQ-60. Material and Methods: Parents of 426 term-born and 1111 preterm-born children from the prospective cohort study Lollipop filled in the Dutch_ASQ-60 and a general questionnaire on educational problems, when the children were 57–63 months old. Dutch cut-off values, reliability and validity (content, construct and concurrent) of the Dutch_ASQ-60 were determined for both the original ASQ score (at least 1 abnormal ASQ Domain-score) and the ASQ-Total score. Furthermore mean domain scores of the Dutch_ASQ-60 were compared with versions in other languages. Results: There were no problems with content validity in an expert meeting. Cronbach's alpha, as measure for reliability was 0.86 for the ASQ-total score. Male gender, prematurity, low paternal education, low family income and small-for-gestational-age (SGA) were associated with abnormal ASQ scores, confirming construct validity. Concurrent validity at age 5 for special educational needs was good for both the original ASQ score (sensitivity 80% and specificity 78%) and the ASQ-Total score (sensitivity 65% and specificity 94%). Area under the curve (AUC) for the ASQ-Total score was 0.86. Mean ASQ-scores for the Dutch_ASQ-60 differed only slightly from other countries: Cohen's delta was above 0.5 for 3 out of 15 comparisons. Conclusion: The Dutch_ASQ-60 has good psychometric properties to screen for developmental problems at age 5 years.